Evaluation of Soluble Tumor Necrosis Factor-Like Weak Inducer of Apoptosis, Omentin, and Tumor Necrosis Factor-α in Subjects with Periodontitis and Type 2 Diabetes Mellitus - Ramasundaram, Vinu; Ponnaiyan, Deepa; Anitha, C M; Prakash, P S G; Victor, D J; Singh, Akanksha (Genetic testing and molecular biomarkers, 2025)
Periodontal disease worsens glycemic control due to the bidirectional link between periodontitis and type 2 diabetes mellitus (T2DM), involving inflammatory markers such as soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK), tumor necrosis factor-α (TNF-α), and omentin-1. However, their combined role in T2DM with periodontitis has not been studied. This study aimed to evaluate the levels of these biomarkers in periodontitis patients with T2DM before and after nonsurgical periodontal therapy (NSPT). Sixty subjects were divided into four groups (15 each): Group I (systemically and periodontally healthy), Group II (systemically healthy with periodontitis), and Groups III and IV (periodontitis with T2DM, exhibiting good glycemic control [hemoglobin A1c (HbA1c) <7%] and poor control [HbA1c >8%]), respectively. Periodontal parameters such as plaque index, bleeding index, probing pocket depth, and clinical attachment level were assessed. Serum samples were collected at baseline and 3 months to measure sTWEAK, omentin-1, and TNF-α levels using ELISA. HbA1c levels were evaluated at baseline and 3 months. TNF-α was significantly elevated in all groups compared with sTWEAK and omentin-1. However, omentin-1 levels were higher in the healthy group compared with all other groups. Periodontal parameters and biomarker levels showed significant improvement across all groups after 3 months post-NSPT. TNF-α and sTWEAK may serve as diagnostic markers, while omentin-1 can be a reliable prognostic marker for evaluating NSPT effects in T2DM patients with periodontitis and varying glycemic control.